1997
DOI: 10.1148/radiology.205.3.9393529
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal submucosal tumors: evaluation with endoscopic US.

Abstract: The differential diagnosis of gastrointestinal submucosal tumors is assisted with endoscopic US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 0 publications
3
34
0
1
Order By: Relevance
“…Reports on objective methods of evaluating echogenicity in gastrointestinal diseases are sparse [10]. Kajiyama et al [18] advocated the method by comparing tumor echogenicity with that of adjacent organs such as the liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on objective methods of evaluating echogenicity in gastrointestinal diseases are sparse [10]. Kajiyama et al [18] advocated the method by comparing tumor echogenicity with that of adjacent organs such as the liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasonography (EUS) has been reported to be an effective modality in the assessment of gastrointestinal neoplasms, enabling us to evaluate the extension and depth of tumor invasion, original layer of submucosal tumor (SMT), homogeneity of internal parenchymal echo, and echogenicity of lesions [1,2,3,4,5,6,7,8,9,10,11,12,13]. Because echogenicity reflects histopathological structure, its evaluation is important to the differential diagnoses of neoplastic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…We postulate that in our case, obesity and diabetes mellitus were significant etiologic factors responsible (7,8). Hepatic disease, chronic pancreatitis and adultonset diabetes mellitus may have been contributory (7,8).…”
mentioning
confidence: 53%
“…Fatty replacement of pancreas may be uniform or may be unevenly distributed, and Langerhans are usually not affected by fatty replacement (4). No etiology has been established for fat replacement of the pancreas; however, several predisposing factors have been suggested: age, obesity, diabetes mellitus, chronic pancreatitis, hepatic disease, dietary deficiency, viral infection, steroid therapy, obstruction of the pancreatic duct, and fibrocystic disease (7,8). Experimental and clinical studies have shown that fat replacement of the pancreas does result from ligation of the pancreatic duct or obstruction of the pancreatic duct by a tumor or a calculus.…”
mentioning
confidence: 99%
See 1 more Smart Citation